Development of a Selective Americium Separation Process Using H4TPAEN as Water-Soluble Stripping Agent. Issue 5 (29th July 2019) - Marie, Cécile; Kaufholz, Peter; Vanel, Vincent; Duchesne, Marie-Thérèse; Russello, Emilie; Faroldi, Federica; Baldini, Laura; Casnati, Alessandro; Wilden, Andreas; Modolo, Giuseppe; Miguirditchian, Manuel
ABSTRACT: Recycling americium from spent nuclear fuel is considered as an important option for a future sustainable nuclear fuel cycle. The PUREX solvent extraction process allows to separate uranium and plutonium from a solution of spent fuel dissolved in nitric acid. In a second step, it would be desirable to separate americium from fission products, and especially lanthanides, but also from curium in order to further transmute americium in future fast neutron reactors. For this purpose, we report the investigation of a new solvent extraction process based on the use of TODGA as an extractant in the organic phase and H4 TPAEN as a selective Am(III) stripping agent in the aqueous phase. With this promising system it is possible to co-extract Am, Cm and lanthanides at high acidity and then selectively strip americium from the loaded organic phase at pH around 1 with H4 TPAEN. Batch extraction data were acquired to evaluate best conditions to develop a liquid-liquid extraction flow sheet. The influence of several parameters like concentration of ligand, cations and temperature on Am(III)/Cm(III) and Am/lanthanides separation was evaluated. Especially, the ability of H4 TPAEN complexing agent to strip macro-concentrations of Am was demonstrated.